The Effectiveness of Audio Visual Media-Based Teaching Materials on Learning Reading Skills of Fiction and Nonfiction Texts - Popon Suryani; Iis Ristiani (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This study aims to determine: 1) the learning outcomes of fiction and nonfiction text reading skills in the control class using conventional teaching materials; 2) the learning outcomes of fiction and nonfiction text reading skills in the treatment class using audio-visual media-based teaching materials; 3) the effectiveness of audiovisual media-based teaching materials in learning fiction and nonfiction text reading skills using audio-visual media-based teaching materials. The method used is descriptive-quantitative. This study was conducted in the odd semester of the 2025-2026 academic year in class V SDN Gekbrong 1. The population consisted of 60 students who participated in learning Indonesian language reading skills across fiction and nonfiction texts. This study used a total sample of 30 class VA students as the control group and 30 class VB students as the treatment group. Data on learning outcomes before and after using audiovisual media-based teaching materials in learning fiction and nonfiction texts were collected using test instruments. Data were analysed using descriptive statistics, namely mean and percentage. The results of the study showed: 1) the learning outcomes of reading fiction and non-fiction texts in the control class using conventional teaching materials reached a mean standard score of 72.79 percent; 2) the learning outcomes of reading fiction and non-fiction texts in the treatment class using audio-visual media-based teaching materials reached a mean standard score of 76.06 percent; 3) the use of audiovisual media-based teaching materials in learning to read fiction and non-fiction texts in grade V of Elementary School was declared effective because the difference in the standard score was relatively significant, namely 13.94. This figure exceeded the 10.00 percent threshold.